Hubungan Hiperlipidemia dengan Kejadian Central Retinal Artery Occlusion: Systematic Review - Khoironi Imada (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Central retinal artery occlusion (CRAO) is an ophthalmologic emergency currently classified as a form of retinal ischemic stroke. Lipid profile disturbances are thought to contribute through atherosclerosis, cholesterol embolism, endothelial dysfunction, and increased thromboembolic susceptibility. This study systematically reviewed the scientific evidence regarding the association of hyperlipidemia with CRAO. A systematic review with narrative synthesis was conducted of observational, cohort, case-control studies, scientific reviews, and scientific statements discussing CRAO or retinal artery occlusion (RAO) and lipid profiles, hyperlipidemia, or dyslipidemia. Available literature indicates that hyperlipidemia is a common comorbidity in CRAO. EAGLE data reported hypercholesterolemia in 49% of patients with non-arteritic CRAO. Another clinical audit found previously undiagnosed hyperlipidemia in 36% of CRAO patients. A Korean national cohort study demonstrated that higher HDL levels were associated with a reduced risk of RAO, while biomarker studies found that elevated LDL-C, non-HDL-C, and ApoB were associated with a higher risk of RAO. Hyperlipidemia is associated with an increased risk of CRAO/RAO, primarily through an atherogenic lipid profile. However, most evidence is observational and often conflates CRAO with RAO in general, thus limiting direct causal inference.Keywords: CRAO, central retinal artery occlusion, hyperlipidemia, dyslipidemia, LDL, HDL, retinal stroke.